Assessing water demand and supply in the Upper Indus Basin using integrated hydrological modeling under varied socioeconomic scenarios - Sareer Ahmad; Muhammad Waseem; Hira Wahab; Abdul Qadeer Khan; Zulqarnain Jehan; Izhar Ahmad; Megersa Kebede Leta (Applied Water Science)
Abstract This study projects future water demand scenarios in the Upper Indus Basin, focusing on reference, high population growth, increased irrigation, and lower population growth scenarios. The baseline scenario indicates a significant rise in water demand from 35.74 billion cubic meters (BCMs) in 2020 to 60.28 BCM by 2035, driven by population growth and increased domestic water consumption. High population growth exacerbates this demand, reaching 62.96 BCM by 2035. This research aims to address domestic water needs under various growth scenarios, considering factors such as population growth rate and per capita consumption. The study employs integrated hydrological modeling to simulate water demand under different socioeconomic conditions. Key methods include analyzing baseline water demand, projecting future scenarios, and evaluating the impact of increased irrigation and population growth on water resources. Results reveal that without intervention, stagnant water supply management will lead to severe water shortages. Increased irrigation, influenced by a 3% growth in irrigated land, pushes agricultural water demand to 56.37 BCM by 2035. Mitigation efforts, such as a 15% reduction in domestic water consumption, could decrease overall demand to 51.23 BCM by 2035. Further reductions are explored through a 50% cut in agricultural water consumption, involving efficient irrigation techniques. The study highlights the critical role of technology and farmer awareness in achieving these reductions, despite current irrigation scheme losses of 20%. A lower population growth scenario shows a contrasting trend, with water demand decreasing to 49.11 BCM by 2035, attributed to a 1.8% population growth rate and decreased per capita consumption to 82 m3 per day. These findings underscore the importance of proactive water management strategies, technological advancements, and demographic considerations in addressing future water demand challenges in the Upper Indus Basin. This research provides proper insight into the impact of varied socioeconomic scenarios on water resources and the necessity for strategic interventions.